Perlawanan Eksekusi Hak Tanggungan di Pengadilan Agama dengan Akad yang Mengandung Klausula Penyelesaian Sengketa melalui BASYARNAS - Ardhi Barkah Apandi; Maimun; Gandhi Liyorba Indra (Reslaj: Religion Education Social Laa Roiba Journal, 2024)
When there is a default committed by the customer, the Islamic Bank can carry out parate execution of the object of mortgage rights used as collateral by the customer through the auction system. The customer often fights against the execution by submitting a fight against execution to the Religious Court, but the contract between the customer and the Islamic Bank which includes a dispute resolution clause through BASYARNAS raises legal certainty issues. The purpose of this research is to find out the authority of the Religious Court in adjudicating cases of resistance to execution even though there is a dispute resolution clause through BASYARNAS in the Deed of Financing Agreement. The method used in this research is a descriptive qualitative method with a conceptual approach and normative approach. Based on the results of the study, it shows that the Religious Court is still authorized to examine, hear and decide disputes against the execution of mortgage rights with a contract containing a dispute resolution clause through BASYARNAS, although article 3 and article 11 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution limit the authority of the Religious Court but BASYARNAS as an arbitration institution does not have the authority to resolve disputes against execution, so that the Religious Court, which has free authority and may not refuse to examine, hear and decide a case because the legal basis for the authority of the dispute is unclear as stipulated in Article 10 of Law Number 48 of 2009 concerning Judicial Power, is still authorized to examine, hear and decide cases.